Dual transitions of toothbrush-like double hydrophilic block copolymers. Issue 3 (12th December 2016) - Sun, Lu; Zhou, Yang; Zhou, Xufeng; Fu, Qiang; Zhao, Sijie; Tu, Xiaoyan; Zhang, Xiaolong; Ma, Liwei; Liu, Mingzhu; Wei, Hua
Abstract : An interesting thermo-regulated dual transition from unimers to vesicles, and finally to micelles, was reported for the first time based on a toothbrush-like double hydrophilic block copolymer. Abstract : An interesting thermo-regulated dual transition from unimers to vesicles, and finally to micelles, was reported for the first time, based on a toothbrush-like double hydrophilic block copolymer (DHBC), poly( N -isopropylacrylamide)- b -poly(oligo(ethylene glycol) monomethyl ether methacrylate) (P(NIPAAm)- b -P(OEGMA)), which was feasibly attributed to the presence of pendent oligo(ethylene glycol) (OEG) brushes and their entanglement with the stimuli-responsive block.